Design of Smart, Compact and Eco-Friendly Waste Disposal Facility for High Density Island of Barrang Lompo - Yashinta Kumala Dewi Sutopo; Mimi Arifin; Sri Aliah Ekawati; Wiwik Wahidah Osman; Gafar Lakatupa; Laode Muh. Asfan Mujahid; Sri Wahyuni; Mukti Ali; Ihsan Ihsan; Iliany Nurul Fitry (Faculty of Engineering UNHAS, 2022)
This paper is part of a Community Service Program aimed to propose a comcept of design of TPS 3R (a Temporary Disposal Facility based on Reduce-Reuse-Recycle concept) that is smart, compact and environmentally friendly for the local people and the waste management/authority of Barrang Lompo Island, Makassar City. The program took about 6 months period, from March to August 2022. The design concept was presented descriptively accompanied with map and layout illustration and has been submitted to the local management/authority on 31 August 2022. The pre- and post-test based on the perspective of 30 spatial planners showed the majority of respondents (87.4%) considered the existing TPS is far from the ideal 5 criteria considered in program. In contrary, the proposed design was highly respected especially the 5th aspect, i.e., how the design encourages the local to creatively produce reused goods e.g., souvenirs. Included in this program was a waste sorting campaign infront of 100 local people invited on 30 July 2022 at 13.00-15.00 PM local time that took place in the front yard of Marine Station of of Unhas.